K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

27 tháng 9 2017

mình chỉ biết làm câu b thôi

x4 - 2x3 + 2x - 1

= (x4 - 1) - (2x3 - 2x)

= (x2 - 1) (x2 + 1) - 2x (x- 1)

(x- 1) (x2 + 1 - 2x)

25 tháng 12 2018

a) (x - y)(x + y + 3).                    b) (x + y - 2xy)(2 + y + 2xy).

c) x 2 (x + l)( x 3  -  x 2  + 2).              d) (x – 1 - y)[ ( x   -   1 ) 2   +   ( x   -   1 ) y   +   y 2 ].

25 tháng 12 2021

\(=a^2b-ab^2+b^2c-bc^2+ac^2-a^2c\)

\(=a^2\left(b-c\right)+bc\left(b-c\right)-a\left(b-c\right)\left(b+c\right)\)

\(=\left(b-c\right)\left(a^2-bc-ab-ac\right)\)

\(=\left(b-c\right)\left[a\left(a-b\right)-c\left(a-b\right)\right]\)

5 tháng 10 2021

\(3,=\left(x-y\right)^3+\left(y-x+x-z\right)^3+\left(z-x\right)^3\\ =\left(x-y\right)^3+\left(y-x\right)^3+3\left(y-x\right)\left(x-z\right)\left(y-x+x-z\right)+\left(x-z\right)^3+\left(z-x\right)^3\\ =\left(x-y\right)^3-\left(x-y\right)^3+3\left(y-x\right)\left(x-z\right)\left(y-z\right)-\left(z-x\right)^3+\left(z-x\right)^3\\ =3\left(y-x\right)\left(x-z\right)\left(y-z\right)\)

\(4,=\left(x^4+3x^3-x^2\right)+\left(3x^3+9x^2-3x\right)-\left(x^2+3x-1\right)\\ =x^2\left(x^2+3x-1\right)+3x\left(x^2+3x-1\right)-\left(x^2+3x-1\right)\\ =\left(x^2+3x-1\right)\left(x^2+3x-1\right)\\ =\left(x^2+3x-1\right)^2\)

17 tháng 7 2021

a) \(x^4+2x^3-4x-4=\left(x^4+2x^3+x^2\right)-\left(x^2+4x+4\right)\)

\(=\left(x^2+x\right)^2-\left(x+2\right)^2=\left(x^2+x-x-2\right)\left(x^2+x+x+2\right)\)

\(=\left(x^2-2\right)\left(x^2+2x+2\right)\)

 

a) Ta có: \(x^4+2x^3-4x-4\)

\(=\left(x^4+2x^3+x^2\right)-\left(x^2+4x+4\right)\)

\(=\left(x^2+x\right)^2-\left(x+2\right)^2\)

\(=\left(x^2+x-x-2\right)\left(x^2+x+x+2\right)\)

\(=\left(x^2-2\right)\cdot\left(x^2+2x+2\right)\)

2 tháng 3 2020

\(ab\left(b-a\right)-bc\left(b-c\right)-ac\left(c-a\right)\)

\(=ab\left(b-a\right)-b^2c+bc^2-ac^2+a^2c\)

\(=ab\left(b-a\right)+c^2\left(b-a\right)-c\left(b^2-a^2\right)\)

\(=\left(b-a\right)\left(ab+c^2-bc-ca\right)\)

\(=\left(b-a\right)\left[b\left(a-c\right)-c\left(a-c\right)\right]\)

\(=\left(b-a\right)\left(a-c\right)\left(b-c\right)\)

14 tháng 8 2016

nhân hả bạn

2 tháng 3 2020

ab(b - a) - bc(b - c) - ac(c - a)

= ab2 - a2b - b2c +  bc2 + ac(a - c)

= b2(a - c) - b(a2 - c2) + ac(a - c)

= b2(a - c) - b(a - c)(a + c) + ac(a - c)

= (b2 - ab - bc + ac)(a - c)

= [b(b - a) - c(b - a)](a - c)

= (b - c)(b -a)(a - c)

2 tháng 3 2020

\(ab\left(b-a\right)-bc\left(b-c\right)-ac\left(c-a\right)\)

\(=ab\left(b-a\right)-\left(b^2c-bc^2\right)-\left(ac^2-a^2c\right)\)

\(=ab\left(b-a\right)-b^2c+bc^2-ac^2+a^2c\)

\(=ab\left(b-a\right)-\left(b^2c-a^2c\right)+\left(bc^2-ac^2\right)\)

\(=ab\left(b-a\right)-c\left(b^2-a^2\right)+c^2\left(b-a\right)\)

\(=ab\left(b-a\right)-c\left(b-a\right)\left(b+a\right)+c^2\left(b-a\right)\)

\(=\left(b-a\right)\left[ab-c\left(b+a\right)+c^2\right]=\left(b-a\right)\left[ab-\left(bc+ac\right)+c^2\right]\)

\(=\left(b-a\right)\left(ab-bc-ac+c^2\right)=\left(b-a\right)\left[\left(ab-bc\right)-\left(ac-c^2\right)\right]\)

\(=\left(b-a\right)\left[b\left(a-c\right)-c\left(a-c\right)\right]=\left(b-a\right)\left(b-c\right)\left(a-c\right)\)